2018
DOI: 10.1007/s00217-018-3049-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a sustainable ultrasound-assisted extraction method for the recovery of polyphenols from lemon by-products: comparison with hot water and organic solvent extractions

Abstract: Response surface methodology (RSM) based on a three-factor and three-level Box-Behnken design was employed for optimizing the aqueous ultrasound-assisted extraction (AUAE) conditions, including extraction time (35-45 min), extraction temperature (45-55 °C) and ultrasonic power (150-250W), for the recovery of total phenolic content (TPC) and rutin from lemon by-products. The independent variables and their values were selected on the basis of preliminary experiments, where the effects of five extraction paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…The TPC results are displayed in Figure 6. applied an US bath to fruit pieces to extract polyphenols by water immersion and found that this extraction reduced the polyphenol content (Papoutsis et al, 2018). Nunes et al (2016) reported that freeze-drying reduced the TPC of guava (Nunes et al, 2016), as was observed in the present study ( Figure 6).…”
Section: Total Polyphenol Content and Antioxidant Activitysupporting
confidence: 79%
See 2 more Smart Citations
“…The TPC results are displayed in Figure 6. applied an US bath to fruit pieces to extract polyphenols by water immersion and found that this extraction reduced the polyphenol content (Papoutsis et al, 2018). Nunes et al (2016) reported that freeze-drying reduced the TPC of guava (Nunes et al, 2016), as was observed in the present study ( Figure 6).…”
Section: Total Polyphenol Content and Antioxidant Activitysupporting
confidence: 79%
“…The effect of sonication only became significant, with increased polyphenol losses, after long US exposure times (90 min) (Mieszczakowska‐Frąc et al, ). Papoutsis et al () applied an US bath to fruit pieces to extract polyphenols by water immersion and found that this extraction reduced the polyphenol content (Papoutsis et al, ). Nunes et al () reported that freeze‐drying reduced the TPC of guava (Nunes et al, ), as was observed in the present study (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process is distinguished by a more effective extraction and use of moderate temperatures of extraction especially beneficial for heat-labile compounds. Several process variables, like applied ultrasonic power, frequency, extraction temperature, reactor characteristics, solvent-sample interaction are considered crucial during USAE [14] and the most amounts of bioactives are reported to be extracted in the initial few minutes of the process. Ultrasound-assisted extraction has been shown to reduce significantly the extraction times, thereby limiting power consumption, as well as enhancing extraction yields in case of many materials [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other by-products from agro-industrial processes have been studied in terms of obtaining phenolic compounds while also using UAE. For example, waste from sunflower oil production, e.g., sunflower seed cake, reached 17.96 mg GAE/g dry TPC biomass in optimised UAE conditions, 43% ethanol, 70 • C and 86 µm amplitude [20], and the residue from lemon juice production produced 17.97 mg GAE/g dry TPC biomass and an antioxidant activity of 9.4 mg TE/g dry biomass in a FRAP assay of extracts that were obtained with UAE at 50 • C, 45 min and 250 W [21]. In both cases, the reported phenolic compound concentrations are lower than those that were obtained with EOP extracts in this work.…”
Section: Process Optimisation and Validation Of The Modelmentioning
confidence: 99%